PENGARUH PERBEDAAN KONSENTRASI LIMBAH CAIR KELAPA SAWIT TERHADAP PERTUMBUHAN DAN KOMPOSISI KIMIA Chlorella Sp. - Dwi Ayu Utami; Tengku Dahril; Windarti Windarti (Fakultas Perikanan dan Kelautan, Universitas Riau, 2020)
The palm oil industry liquid waste is rich in organic materials and thus it can be used as media to grow Chlorella sp. This algae needs organic materials for growing, and it may decrease the organic material contents in the waste. To understand the best concentration of palm oil industry liquid waste to grow that algae, the chemical composition of the algae reared in different concentration of waste, and to understand the organic materials decrement in the waste, a study has been conducted in April – May 2019. There was a CRD applied. The waste was mixed with aquadest in 5 different concentration, namely P1 (0%), P2 (15%), P3 (20%), P4 (25%), dan P5 (30%). Results shown that the best algae population was in the P4 (4.64 x 106 cells/mL), the best biomass was in P3 (0.77 gr/L) in the 12nd day culture. The P0 provide the best results on fat (12.5%) and carbohydrate (24%) but shown the lowest of protein (16%), DO (1.10 mg/L) and chlorophyll-a (0.140 mg/L) and provide the worst CO2 content (8.77 mg/l). P3 shown the highest content of protein (45%). P4 shown the highest chlorophyll-a concentration (0.403 mg/L) and O2 concentration (9.94 mg/L) and the lowest CO2 (2.75 mg/l). The P4 also shown the best result in decreasing organic materials content. Nitrate reduced, from 14.3 mg/L into 3.1 mg/L, while Phosphate reduced, from 1.87 mg/L to 0.33 mg/L respectively. In all treatment, the water temperature ranged from 280C to 300C and the pH was 6.33 – 9.50.